2000
DOI: 10.1152/ajpregu.2000.279.4.r1449
|View full text |Cite
|
Sign up to set email alerts
|

Portal GLP-1 administration in rats augments the insulin response to glucose via neuronal mechanisms

Abstract: The incretin glucagon-like peptide-1 (GLP-1)-(7---36) amide is an important factor in prandial glucose homeostasis. Findings that GLP-1 is rapidly inactivated led to the hypothesis that the target of GLP-1 is close to the site of release. To investigate whether the target tissue is located in the hepatoportal system, we administered GLP-1 with glucose into the portal vein of rats and compared this with peripheral GLP-1 administration (jugular vein) and studied the effects of blockers of the nervous system. Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 17 publications
8
130
0
2
Order By: Relevance
“…Analogous to the interpretation above, however, it may be that intraperitoneal GLP-1 affects more than one population of NTS neurons, one of which has a 2CR input and is necessary for satiation and the other of which expresses c-Fos but is not sufficient for satiation. One possibility is that this latter population contributes to GLP-1's incretin response, which also appears to involve vagal afferent signaling (7,32).…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to the interpretation above, however, it may be that intraperitoneal GLP-1 affects more than one population of NTS neurons, one of which has a 2CR input and is necessary for satiation and the other of which expresses c-Fos but is not sufficient for satiation. One possibility is that this latter population contributes to GLP-1's incretin response, which also appears to involve vagal afferent signaling (7,32).…”
Section: Discussionmentioning
confidence: 99%
“…This has given rise to speculations that the actions of GLP-1 on the beta cells might be exerted indirectly via activation of long vago-vagal reflexes (53). Indeed, the GLP-1 receptor is expressed in cell bodies in the nodose ganglion from which the sensory afferents from the GI-tract emanate (55), and it has been demonstrated that blockade of the autonomic ganglia also blocked the effects of intraportally injected GLP-1 on insulin secretion (56). Thus it may be that under physiological conditions the majority of the effects of GLP-1 on insulin secretion is transmitted via autonomic nerves.…”
Section: Reflex Activation Of the Beta Cellmentioning
confidence: 99%
“…15 The hepatoportal sensor has been shown to control multiple physiological function. 5 Its activation stimulates first-phase insulin secretion, 16,17 increases hepatic glucose clearance, 18 stimulates, in an insulin-independent manner, peripheral tissue glucose uptake, 8,19 suppresses glucagon secretion (see below) and terminates feeding. 20,21 Thus, the combination of physiological as well as pharmacological and genetic studies has provided strong evidence for an important role of the hepatoportal sensor in the regulation of several homeostatic functions.…”
Section: Sites and Mechanisms Of Glucose Sensingmentioning
confidence: 99%